Factors influencing mask use and physical distancing for COVID-19: A qualitative evidence synthesis - Dachi I. Arikpo; Okwu A. Onyema; Afiong O. Oku; Chibueze Meremikwu; Hannah Hamilton-Hurwitz; João P. Toledo; Kathleen Dunn; April Baller; Helen J. Smith; Martin M. Meremikwu (Journal of Public Health in Africa)
Background: The World Health Organization (WHO) recommends a bundle of precautions to reduce community transmission of COVID-19, including mask use and physical distancing. However, there is evidence that suggests poor adherence to these health measures community settings.